PROBLEMATIKA PERALIHAN KURIKULUM 2013 MENUJU KURIKUUM MERDEKA TERHADAP KEMAMPUAN NUMERIK SISWA - Jihaan Mariza; Leni Khusniah; Patmawati Patmawati; Hilyati Aulia (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
The curriculum is a guideline for carrying out learning activities in order to achieve educational goals, because basically the curriculum is the foundation so that education always experiences renewal. Therefore, the independent curriculum was born and initiated by the new government, namely the Ministry of Education and Culture. The purpose of this study was to determine the transition of the curriculum, the teacher's adaptation process, and the obstacles in the transition from the K13 curriculum to independent learning. The method used is a qualitative method, in this study using documentation techniques, in-depth interviews as well as observation. The conclusion from the results of the analysis is: the independent learning curriculum at SDN 55 Sridadi has been implemented starting in the final 2021 school year, taking into account several factors, then preparing teaching tools. The process of adapting mathematics teachers is carried out by applying Pancasila student profiles in learning and participating in several trainings to improve teacher abilities. The obstacles to this transition lie in human resources, teacher abilities, and differences in understanding, thinking and ways of thinking of students in understanding the independent curriculum.